Les paradoxes des droits reproductifs au Brésil: avortement et stérilisation féminine - Scavone, Lucila; Bateman, Simone; Le Doaré, Hélène (Cahiers du Genre, 1999)
Cet article rend compte du débat mené au Brésil autour des droits reproductifs et souligne les avancées et les contradictions particulières de deux problèmes que rencontrent actuellement les femmes brésiliennes : la stérilisation et la pratique illégale de l’avortement. Il met en évidence que la pratique généralisée de la stérilisation féminine et le nombre des avortements clandestins, qui représentent un risque pour la santé des femmes, révèlent les carences de la politique de la santé sur le plan des choix reproductifs et de la politique de contrôle démographique. Il montre les diverses orientations prises par ce débat à la fin des années quatre-vingt-dix et la nécessité de se réapproprier sa dynamique de transformation sociale.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du sud; approches et analyses; brésil; corps; cours; discipline; discours dominant; droits des femmes*; justice reproductive; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Engels et l'émancipation des femmes - Europe Solidaire Sans Frontières - Trat, Josette (Engels et savants révolutionnaires, 1997)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1970-1979; approches et analyses; capitalisme; classe ouvrière; corps; cours; discipline; europe; famille; france; justice sociale; marxisme; premier cycle; périodes historiques; russie; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
https://www.deslibris.ca/ID/412587
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques